A compact Ka‐band limiter‐low noise amplifier MMIC with high power capability. Issue 6 (11th March 2022) - Yang, Lin; Zhang, Ming; Wang, Jianchao; Wang, Baozhu; Yu, Pingping; Wu, Ruihong
Abstract: This paper presents a 30–36 GHz limiter low‐noise amplifier (limiter‐LNA) MMIC for high power and high mobility millimeter‐wave radar systems. The PIN‐diode limiter network and the LNA are codesigned to realize high input‐power handling capability, good small‐signal performance, and small chip area. A two‐state matching capacitor is presented to improve both the input‐power handling capability at the high input‐power level and the input return loss at the small‐signal level. The proposed circuit is fabricated with a combined PIN/0.15‐µm‐GaAs‐pHEMT process. The limiter‐LNA is capable of handling 39 dBm continuous wave (CW) input‐power without failure with only two limiter stages. The measured noise figure is 1.8–2.5 dB, the small‐signal gain is 18.5 ± 0.5 dB, the output power at 1 dB compression point is larger than 11 dBm, and the dc power consumption is 72 mW. The chip area, including testing pads, is only 2.1 mm × 1.0 mm. This limiter‐LNA MMIC is believed to have the highest input‐power handling capability and smallest chip area among limiter‐LNA MMICs at this frequency range reported up to date.